Pendidikan Multikultural sebagai Landasan Pengembangan Karakter untuk Mempersiapkan Gen Z di Tengah Perbedaan Budaya - Abdul Hadi; Nurhidayati Nurhidayati; Nurainun Nurainun; Satria Wiguna (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
This study aims to analyze the role of multicultural education in shaping the character of generation Z in the midst of cultural diversity, with a focus on STAI Jam'iyah Mahmudiyah Tanjung Pura students. This research uses a qualitative method with a descriptive approach through the implementation of interactive seminars. This activity involved material presentation by resource persons, group discussions, and case study analysis to encourage understanding and application of multicultural values. The results showed that the seminar succeeded in raising students' awareness of the importance of tolerance, empathy, and respect for differences. In addition, students realized the need for practical skills in applying these values in their daily lives. The activity also revealed that although students have a good theoretical understanding, they need more opportunities for hands-on cross-cultural experiences. The implementation of multicultural education that involves real-life experiences is considered important to prepare the younger generation to face global challenges and build an inclusive society.